31 Gametic Incompatibility: Improving the Success of Mate Allocation in Dairy Cattle. (8th October 2021) - Martin, Audrey A A; Id-Lahoucine, Samir; Tulpan, Dan; Leblanc, Stephen J; Cánovas, Angela; Baes, Christine F; Schenkel, Flavio S
Abstract: In the dairy industry, mate allocation is mainly based on the parents' breeding values and inbreeding coefficients aiming to achieve the producer's breeding goal. With artificial insemination, the portfolio of sires to choose from is large and the quality of the semen doses is standardized. However, not all sire-dam matings are equally likely to produce a successful pregnancy. Among other reproduction issues, the success of a mating could vary due to the incompatibility of gametes coming from the sire and the dam and could influence the fertilization's success, additionally to the reproductive capacity of the parents. Considering the gametic incompatibility of the potential parents could be a novel option to improve mating plans. Under the hypothesis that gametic incompatibility has a significant effect on reproduction and reduces the odds of fertilization and pregnancy, this study aimed to determine the genetic background of gametic incompatibility. Transmission ratio distortion (TRD), which detects deviations from Mendelian inheritance expectations, is commonly used to identify deleterious mutations. We adapted the TRD model by including an interaction effect between the gametes leading to the offspring genotype to detect regions with TRD effects and gametic incompatibility. Our dataset contained 436, 651 genotyped (50K SNP) Canadian Holstein cattle from 283, 817 parents-offspring trios. A total of 482 regions with TRD containing 671 positional genes were found. The functional analysis detected biological pathways associated with uterus development, embryonic skeletal system development, and nervous system development. Additionally, gene ontology terms from the topology-based pathway enrichment analysis were mostly related to the steroid hormones signalling pathway. Although difficult, genes specific to gametic incompatibility could be differentiated from genes underlying other reproduction processes by refining the genetic regions with TRD. With further investigation, we will provide new information to improve mate allocation for the dairy cattle industry.